RANCANG BANGUN PENGERING PADI HYBRID SOLAR DRYER DAN PANEL SURYA - Pratama, Wisnu; shidqi khaerudini, deni (TURBO [Tulisan Riset Berbasis Online], 2024)
Rice drying in Indonesia generally still uses conventional methods by utilizing the heat of sunlight, but weather changes become a problem in the drying process, so that the rice drying process is hampered. Based on this, the purpose of this study is to develop a hybrid solar dryer and solar panel rice drying system. The method used in this study is an experimental method using a design in the form of a cabinet dryer type drying room with a fairly simple design and installation of equipment. Flow simulations were carried out using Autodesk Simulation software, namely Computational Fluid Dynamic (CFD). Three trials were carried out. In trial 1, there was a decrease in humidity of 30%, in trial 2, there was a decrease in humidity of 20% and in trial 3, there was a decrease in humidity of 51% percent. In the third trial, the temperature after drying reached 59.1 ° C, much higher than the first (34.4 ° C) and second (44.9 ° C) trials. Based on the research results, it can be concluded that the process of drying rice using a hybrid solar dryer and solar panels with a drying duration of 2-3 hours with a combination of solar energy and solar panels can achieve optimal results. Sufficient time and high temperatures play an important role in reducing humidity. The level of efficiency of drying rice using a hybrid solar dryer and solar panels has been proven to be able to reduce rice humidity significantly, with the highest humidity reduction achieved in the third trial of 51% which shows that this drying system is effective in reducing water content in rice.